Diseño de un sistema de control interno para empresas de comercialización de neumáticos y servicios mecánicos. Caso :Empresa Llantamatic Compañía Limitada - López Cevallos, Erika Maribel (2015)
Today organizations interact in a globalized and changing world, which are required to be in constant evolution, this is the case Llantamatic company Cia. Ltda. Dedicated to the marketing of tires and mechanical services, thanks to the demand in the market has been growing. The company has grown and changed a lot in recent years, though there have been no changes in the structure and operation, this causes unrest among the employees because they have clear roles, activities and processes to be performed. The company needs a system of internal control that suits their nature, characteristics and needs. The internal control system helps the activities and processes are met efficiently and effectively, generating timely information for making important decisions, which are directly related to achieving the objectives. Therefore this paper proposes a system of internal control for the company, considering the weaknesses in it. This system will be implemented by management, will enable the efficient development of operations, giving managers and employees a written manual that can find control policies, functions and processes that work in the company.